2019
DOI: 10.2139/ssrn.3473394
|View full text |Cite
|
Sign up to set email alerts
|

Information, Technology, and Digitalization in China’s Environmental Governance

Abstract: Research on the relationship between information, technology, and environmental governance in the current Information Age has gained momentum in recent years. Nevertheless, much theoretical, empirical, and normative issues remain seriously under-explored. Existing studies also tend to be predominantly based on contexts, experiences, and lessons in advanced democratic societies. What the rapid developments in new information technologies, data, and information networks might mean for environmental politics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This cluster contains 37 articles. For example, Kostka et al [66] found that under the background that the role of information has evolved over time as the dominant environmental regulatory approach has changed, the performance of new information technologies in China has so far been simple. Although some similarities can be drawn between advanced democracies and China, many predictions about the impact of data and information technology have not yet been confirmed in China.…”
Section: Cluster Identification and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This cluster contains 37 articles. For example, Kostka et al [66] found that under the background that the role of information has evolved over time as the dominant environmental regulatory approach has changed, the performance of new information technologies in China has so far been simple. Although some similarities can be drawn between advanced democracies and China, many predictions about the impact of data and information technology have not yet been confirmed in China.…”
Section: Cluster Identification and Analysismentioning
confidence: 99%
“…Third, China has a big gap with developed countries in terms of environmental disclosure quality and ET implementation effect. As Kostka et al [66] put forward when discussing the impact of information technology on environmental regulation, although some similarities can be drawn between advanced democracies and China, many predictions about the impact have not been seen in China. Although one may actively learn from the ET experience of developed countries, it should compare the specific differences between developing countries and developed countries and ponder the reasons for the differences, so that it is possible to find the most suitable path based on the real situation of a developing country.…”
Section: Constructing Knowledge Graph For Etmentioning
confidence: 99%